Aggregation of mineral particles in cryoconite granules by multiple species of cyanobacteria on Urumqi Glacier No.1, China - Chen, Yunjie; Takeuchi, Nozomu; Tanaka, Sota; Li, Zhongqin (Frontiers in Earth Science, 2025)
Cryoconite granules are microbial aggregations formed by filamentous cyanobacteria with mineral particles on the bare ice surface of glaciers worldwide. Multiple species of filamentous cyanobacteria in cryoconite granules can usually be microscopically and phylogenetically identified. However, the roles of each species in the formation process of granules remain unclear. In this study, the compositions of filamentous cyanobacteria and minerals, as well as the microstructure of cryoconite granules of different sizes collected on a mountain glacier in central Asia, were analyzed. Three distinct morphological taxa of filamentous cyanobacteria (Types A, B, and C) were observed in cryoconite granules, with Types B and C being dominant across all size fractions. Scanning electron microscope observation revealed that Type B often had abundant small mineral particles on its filament surface, while Type C was mostly without or with only a few mineral particles. Abundant clay minerals were found in all size fractions of granules. Our results suggest that cyanobacterial taxa play a different role in binding mineral particles within cryoconite granules and that the presence of multiple taxa of filamentous cyanobacteria contributes to the effective growth of these granules on the glacier surface.